Oracle Web Application Programming for PL/SQL Developers. - Boardman, Susan K.; Caffrey, Melanie; Morse, Solomon; Rosenzweig, Benjamin (Prentice Hall PTR Oracle Ser., 2002)
Oracle Web Application Programming for PL/SQL Developers is the hands-on, rapid-mastery guide to Oracle PL/SQL Web development. Learn the core pieces you need to know, from the basics of configuring the Oracle Internet Application Server to PL/SQL Server Pages and the PL/SQL Web Toolkit. The book covers testing, debugging, troubleshooting, deployment, and maintenance and contains practical examples, hands-on exercises, and dozens of practical tips from expert developers.